1999
DOI: 10.1007/s001980050229
|View full text |Cite
|
Sign up to set email alerts
|

Premature Greying of the Hair Is Not Associated with Low Bone Mineral Density

Abstract: In two recent case-control studies premature greying of the hair was associated with a lowering of bone mineral density (BMD) and osteopenia, suggesting that this might be a clinically useful risk marker for osteoporosis. We report a further re-examination of this proposal in 52 prematurely grey-haired women from East Yorkshire who responded to an advertisement inviting them for bone densitometry. Thirty-five had no clinical or drug history that could influence bone density. All were Caucasian with a mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Premature greying may be a weak marker for reduced bone mineral density (BMD) in women with a history of Graves' disease, but it is not a marker in normal women [33]. But later studies showed no such link [34].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Premature greying may be a weak marker for reduced bone mineral density (BMD) in women with a history of Graves' disease, but it is not a marker in normal women [33]. But later studies showed no such link [34].…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…[ 4 5 ] However, some studies showed that there is no correlation between the two. [ 6 7 ] We conducted a case–control study to compare the degree of osteopenia in healthy individuals with premature graying of hair (PGH) and those without PGH.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, well-known conditions in menopausal women are decrease in Bone Mineral Density (BMD) and Hair-Loss (HL) because the loss of physiological levels of estrogens and androgens [5]. Some risk factors for osteoporosis such as age, sex, race, family history, early menopause, oophorectomy, prolonged amenorrhea, lack of physical exercise and bone depleting medical conditions have been accepted, but it has been considered that these factors do not predict all of the observed changes in BMD and the factors should be better defined [6]. In our daily practise, during the detection of etiopathological reasons in AGA patients, we noticed that a significant number of women had joint complaints in their systematical examinations.…”
Section: Introductionmentioning
confidence: 99%